Severe mental disorders in rural China: a longitudinal survey. (December 2017) - Ran, Mao-Sheng; Weng, Xue; Liu, Yu-Jun; Zhang, Tian-Ming; Thornicroft, Graham; Davidson, Larry; Chui, Cheryl H.K.; Hu, Shi-Hui; Yang, Xin; Lin, Fu-Rong; Liu, Chang-Cheng; Liu, Bo; et al.
Abstract: Background: Little is known about the change in long-term prevalence of mental disorders during a period of sustained rapid socioeconomic development. Here we explore the prevalence change of severe mental disorders in a 21-year longitudinal study in a rural area of China. Methods: Epidemiological surveys of mental disorders were done in May, 1994, and October, 2015, in six townships (total population 170 174 in 2015) in Xinjin County, Chengdu, China. Psychoses Screening Schedule (PSS) together with key informant method for household survey and general psychiatric interview were administered to identify the persons with severe mental disorders according to International Classification of Mental and Behavioural Disorders-10 (ICD-10) criteria. Findings: Among all persons aged 15 years and older, the age-standardised lifetime prevalence of all mental disorders increased 48·2% from 870·1 per 100 000 population (95% CI 811·3–928·9 per 100 000 population) in 1994 to 1289·4 per 100 000 population (1218·0–1360·8 per 100 000 population) in 2015. The age-standardised lifetime prevalence of schizophrenia was the highest among all mental disorders and remained relatively stable from 1994 (416·0 per 100 000 population) to 2015 (427·9 per 100 000 population). Between 1994 and 2015, the age-standardised lifetime prevalence increased for affective disorders (41%), alcohol dependence and alcoholism (373·8%), drug and substance abuse (1809%), and mental disorder plus cerebrovascular disease (214%), brain trauma (388%), and senile dementia (126%). Moreover, age-standardised lifetime prevalence was significantly higher in men (1465·5 per 100 000 population) than in women (1179·0 per 100 000) in 2015 (p<0·0001). Interpretation: Various mental disorders in people living in the rural community display different trends from 1994 to 2015. Although the age-standardised lifetime prevalence of all causes disorders increased from 1994 to 2015, the prevalence of schizophrenia remained relatively stable. Prevalence of affective disorders, alcohol dependence and alcoholism, drug and substance abuse, senile dementia, and other organic disorders increased sharply, possibly indicating the effect of socioeconomic development on mental disorders. Mental health policy and services should be improved and adjusted according to the prevalence change of mental disorders. The limitations of this study include: (1) the sample investigated was from one rural area of China; (2) only two surveys were done; and (3) as many young people in this rural area might move to work temporarily in urban areas, the final reported prevalence might underestimate the true prevalence in young people. Funding: The investigation in 1994 was supported in part by the China Medical Board of New York (CMB, 92-557, to MZX). The investigation in 2015 was supported in part by Seed Funding Programme for Basic Research (HKU, 2014-2016, to MSR), Seed Funding Programme for Applied Research (HKU, 2014-2016, to MSR), Strategic Research Theme (SRT): Contemporary China Seed Funding (HKU, 2014-2016, to MSR), Small Project Funding (HKU, 2014-2016, to CLWC), and Mental Health Research in Chengdu, China (Dept. Matching Fund, 2015-2017, to MSR).